Mental Health Status of Paediatric Medical Workers in China During the COVID-19 Outbreak - Liu, Yin; Wang, Li; Chen, Long; Zhang, Xianhong; Bao, Lei; Shi, Yuan (Frontiers in Psychiatry, 2020)
Background: A novel coronavirus (COVID-19) outbreak has occurred in China, and national medical workers have been thrown into this silent battle. Paediatric medical workers have been an important part of this battle and under enormous pressure. This paper evaluates the depression, anxiety, and stress of paediatric medical staff during the epidemic and examines related impact factors. Methods: We conducted this study using online questionnaires via social networking software during the week of Feb. 17 to Feb. 23, 2020. The 21-item Depression Anxiety Stress Scale (DASS), which is a revised, simplified version of the original DASS developed by Lovibond et al., was used in this study. Results: Among all 2031 respondents, 14.81%, 18.3% and 9.98% had depression, anxiety and stress symptoms, respectively. Males, doctors, individuals aged between 31-60 years, those with senior job titles, those who had contact with patients with confirmed or suspected cases of COVID-19, those who worked on the clinical frontlines fighting the epidemic and those who had experience combating similar outbreaks were more likely to have depression, anxiety or stress symptoms. Respondents in Beijing and Chongqing had lower negative psychological symptom scores than the national average. Conclusion: During the COVID-19 outbreak, depression, anxiety and stress are present to varying degrees among paediatric medical workers across the country. Psychological crisis interventions should be implemented to protect the mental health of paediatric medical workers during and after the epidemic.